1923: Was Architecture a branch of Engineering? - Sambricio, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Toward the end of the First World War, after the flow of migration from the countryside to the city, the number of housing units built in the historic city center and the newer sections of the city hardly varied, while the number of units on the outskirts grew. As a result of this growing number the Town Hall assumed that the lack of housing was a municipal problem and those in charge of construction saw the building of low-cost housing as a profitable business. All of this took place during a time when architects were still debating the possibility of a national style.
Keywords: Social housing; Prefabrication; Standardization; Housing Policy; The 1923 Affordable Housing Law